Pengaruh Price, Product Diversity, dan Product Quality terhadap Repurchase Intention Customer pada Minimarket Indomaret Fresh di Kota Medan - Kevin Samuel Benammi Brahmana; Hafiza Adlina; Onan Marakali Siregar (Jurnal bintang manajemen, 2025)
The modern retail industry in Indonesia is increasingly competitive, especially in the minimarket sector, which requires every business actor to continuously improve the quality of services and products to maintain consumer loyalty. Indomaret, as one of the main players, has introduced the Indomaret Fresh concept that offers a wider variety of products and a more modern shopping experience. However, despite various innovations, there are still complaints from consumers regarding prices, product diversity, and product quality available. This study aims to analyze the influence of price, product diversity, and product quality on consumer repurchase intentions at Indomaret Fresh in Medan City. The study used a quantitative approach with data collection through questionnaires distributed to 100 respondents, and data analysis was conducted using SPSS to test the partial and simultaneous effects of these variables. The results showed that price and product diversity had a negative and insignificant effect on repurchase intentions, while product quality had a positive and significant effect. Simultaneously, these three variables together had a significant effect on repurchase intentions. These findings emphasize that product quality is a major factor in building consumer loyalty, while aspects of price and product variety need to be adjusted to consumer preferences and expectations for a more effective Indomaret Fresh marketing strategy.